PENGARUH PENGGUNAAN TEPUNG DAUN DAN BATANG UBI JALAR (VINES) DALAM RANSUM TERHADAP KECERNAAN LEMAK DAN SERAT KASAR PADA TERNAK BABI - Yigibalom, Maikel; Rahasia, C.A.; Pontoh, Ch. J. (ZOOTEC, 2018)
THE EFFECT OF USING SWEET POTATO LEAVES (VINES) IN RATIONS ON DIGESTIBILITY FAT AND CRUDE FIBER IN PIGS. Pig livestock is one of the commodities that has great potential to be developed because it has beneficial properties, namely the ability of pigs to convert food ingredients more efficiently. A study has been carried out to determine the effect of using sweet potato leaves (vines) in rations on digestibility fat and crude fiber in pigs. This research was conducted for 50 days, from June 20 to August 9, 2017. This study used 5 (five) castrated male pigs from crosses of Duroc X Spotted Poland China around 3.5-4.0 months old, 30 kg initial weight: The treatment ration formulated as follows: R0 = 100% Basic Ration + 0% Leaves and Stems of Sweet Potatoes R1 = 92.5% Basic Ration + 7.5% Sweet Potato Flour and Stems R2 = 85% Basic Ration + 15% Sweet Potato Leaf and Stem Flour R3 = 77.5% Basic Ration + 22.5% Leaf and Stem Flour Sweet Potato R4 = 70% Basic Ration + 30% Leaf Flour and Sweet Potato Flour. Parameters observed were fat and crude fiber digestibility. The use of sweet potato leaves and stems flour did not have significant effect (P> 0.05) on the digestibility value of crude fiber and fat. The use of sweet potato leaves and stems gave significantly different effects (P <0.05) on the digestibility value of crude fiber and fat or at least one different pair. It can be concluded that the leaves and stems of sweet potatoes (vines) can be used up to 30% in the ration of castrated male pigs. without negative effects on fat digestibility and crude fiber ration.Â Keywords: sweet potato leaves, digestibility, pig